Expediente (Revista do Tribunal Regional Federal da 3ª Região, 2012)
DIRETOR DA REVISTA: Desembargador Federal Antonio CedenhoASSESSOR: Wladimir RodriguesEQUIPE:Lucia Massako Y. C. RosaMaria José Lopes LeiteRafael Leal FerreiraRenata Bataglia GarciaSimone de Alcantara Savazzoni
Keywords: expediente; v. 23; n. 113; maio/jun. 2012